Promoting health and productivity management in small companies through outreach-based public-private partnership: the Yokohama Linkworker Project - Kai, Yuko; Fujii, Yuya; Takashi, Naoki; Yoshiba, Kaori; Muramatsu-Noguchi, Yuko; Noda, Takayuki; Jindo, Takashi; Kidokoro, Tetsuhiro; Yajima, Yoko; Kasuga, Junko; Arao, Takashi (Frontiers in Public Health, 2024)
Introduction With health promotion initiatives in small companies lagging behind those in larger corporations, strengthening health and productivity management in small companies through innovative strategies is an urgent priority. We hypothesized that an outreach strategy involving a public-private partnership would be beneficial for this purpose. The present study examines the implementation of a public-private partnership strategy in Yokohama City, Japan, assessing its impact on health and productivity management in small enterprises, focusing on implementation outcomes. Methods As part of the Yokohama Linkworker Project (Y-Link Project), this study describes and examines a public-private partnership program in Yokohama City, Japan, involving the city’s government and a private life insurance company. Trained insurance sales representatives served as “Linkworkers” for the program, reaching out to small enterprises in the city. These Linkworkers provided tailored support to these companies, assisting them with obtaining the “Yokohama Health and Productivity Management Certification” issued by the City of Yokohama authorities and collaborating with external entities to offer health promotion programs for employees. Program interventions took place from August to September 2020. The RE-AIM framework was utilized to evaluate the Project. Data were extracted from Linkworkers’ activity records, certification records, the Linkworker survey, and follow-up surveys with participating companies at 6– and 18– months post-interventions. Results Within 2 months, 71 Linkworkers visited 500 companies (50% were small firms, <50 employees). Among them, 224 (45%) enterprises received certifications, contributing to an increased regional certification rate. Linkworker-assisted companies tended to be significantly smaller in size. The odds ratios of implementing workplace health promotion programs in certified firms, compared to non-certified firms, were 4.09 (95% CI: 1.79–9.35) at 6 months and 2.31 (95% CI: 1.04–5.11) at 18 months. For small firms, the odds ratios were 6.87 (95% CI: 1.74–27.06) at 6 months and 3.42 (95% CI: 1.17–10.03) at 18 months. The certification retention rate at 24 months was 60%, irrespective of company size. Linkworkers perceived the outreach strategy as having a positive impact on their primary operations. Conclusion The Y-Link Project’s outreach strategy enhanced health and productivity management in small enterprises in Yokohama City, enabling long-term health promotion programs addressing program availability disparities related to company size.